ANALYSIS OF THE IMPACT OF MONETARY POLICY AND TRANSMISSIONMECHANISMS ON ECONOMIC GROWTH IN INDONESIA: AN EMPIRICAL APPROACH USING VAR (VECTOR AUTOREGRESSION) MODEL - Loso Judijanto; Caroline; Ahmad Rizani; Umar Kholil Lubis; Zet Abdullah (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This research investigates the intricate relationship between monetary policy, transmission mechanisms, and economic growth in Indonesia using an empirical approach employing the Vector Autoregression (VAR) model. In the ever-evolving landscape of global economics, the role of monetary policy in promoting stability and growth is pivotal, especially for emerging economies like Indonesia. The study delves into the specific context of Indonesia, a country that has experienced periods of economic growth amid challenges such as fluctuating inflation rates, exchange rates, and external shocks. The research explores how the central bank, Bank Indonesia, employs monetary policy tools to navigate these challenges and assesses the impact of these policies on the nation's economic growth. Furthermore, it examines the transmission mechanisms propagating these effects, including interest rates, exchange rates, and bank lending. It also scrutinizes the presence of time lags, the magnitude and direction of these effects, and the influence of external factors. The findings of this study are expected to have significant implications for policymakers, central banks, investors, and the broader academic community. Understanding monetary policy dynamics in a globalized world marked by economic volatility is critical for making informed policy decisions.